Testing the waters a documentary about the process : a future for Niagara River - Corcoran, Lynn; Corcoran, Lynn; Corcoran, Lynn; Keefe, Dennis (Oley, pennyslvania : Bullfrog Films, 1988)
Considers the future of the Niagara River which is threatened by toxic chemical wastes, and examines the competing interests of industry, government, and citizens in disposing of and dealing with toxic wastes
Keywords: Hazardous wastes -- Niagara River (N.Y. and Ont.); Water -- Pollution -- Niagara River (N.Y. and Ont.)